AI-POWERED INNOVATION IN DEPARTMENTAL STORES: A STUDY OF ITS INFLUENCE ON CUSTOMER EXPERIENCE, EFFICIENCY, AND BUSINESS GROWTH - Desai, Krushita; Mehta, Mona (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Several industries are changing as a result of AI-driven innovation that improves efficiency, sustainability, and decision making. This shift is occurring in East Government, Robotics, workplaces, industry and mobile networks. AI’s capacity to automate processes, optimized resources, and stimulate creativity is primarily responsible for these advancements. The retail business has seen a shift thanks to artificial intelligence (AI), which has created new potential for continuous service delivery, service quality improvement, and personalization. This research papers goal is to assess AI powered innovation in department stores and how it affects consumer satisfaction, productivity, and company expansion. The present study used structural equation modelling as its methodology. The study’s conclusions showed that the department stores integration has a major effect on customer satisfaction, business expansion, and efficiency.